Aurora Kinase Inhibitors: Current Status and Outlook - Bavetsias, Vassilios; Linardopoulos, Spiros (Frontiers in Oncology, 2015)
The Aurora kinase family comprises of cell cycle-regulated serine/threonine kinases important for mitosis. Their activity and protein expression are cell cycle regulated, peaking during mitosis to orchestrate important mitotic processes including centrosome maturation, chromosome alignment, chromosome segregation and cytokinesis. In humans, the Aurora kinase family consists of three members; Aurora-A, Aurora-B and Aurora-C, that each share a conserved C-terminal catalytic domain but differ in their sub-cellular localization, substrate specificity and function during mitosis. In addition, Aurora-A and Aurora-B have been found to be overexpressed in a wide variety of human tumors. These observations led to a number of programs among academic and pharmaceutical organizations to discovering small molecule Aurora kinase inhibitors as anti-cancer drugs. This review will summarize the known Aurora kinase inhibitors currently in the clinic and the current and future directions.